Maimonides Review of Philosophy and Religion Volume 1, 2022 - Strauss, Ze'ev (Brill, 2022)
The Maimonides Review of Philosophy and Religion is an annual collection of double-blind peer-reviewed articles that seeks to provide a broad international arena for an intellectual exchange of ideas between the disciplines of philosophy, theology, religion, cultural history, and literature and to showcase their multifarious junctures within the framework of Jewish studies. Contributions to the Review place special thematic emphasis on scepticism within Jewish thought and its links to other religious traditions and secular worldviews. The Review is interested in the tension at the heart of matters of reason and faith, rationalism and mysticism, theory and practice, narrativity and normativity, doubt and dogma. This volume features contributions by Reimund Leicht, Gitit Holzman, Jonathan Garb, Anna Lissa, Gianni Paganini, Adi Louria Hayon, Mark Marion Gondelman, and Jürgen Sarnowsky. This volume features contributions by Jeremy Phillip Brown, Libera Pisano, Jeffrey G. Amshalem, Maria Vittoria Comacchi, Jonatan Meir, Rebecca Kneller-Rowe, Isaac Slater, Michela Torbidoni, Guido Bartolucci, and Tamir Karkason.